2021
DOI: 10.1111/ibi.12910
|View full text |Cite
|
Sign up to set email alerts
|

The role of wind fetch in structuring Antarctic seabird breeding occupancy

Abstract: Avian breeding sites located along shorelines may allow easy access to aquatic food sources, but risk exposing birds and nests to high wind and wave action. One measure of exposure is wind fetch, the distance of open water over which wind can blow uninterrupted. By calculating fetch weighted by prevailing wind direction for breeding colonies of pursuit‐diving seabirds in the Antarctic Peninsula, we show that different members of this guild have opposing relationships to coastline exposure. Gentoo Penguins Pygo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Overall, therefore, our results show that CFD can be used to predict occupancy directly or combined with other approaches, such as the use of orientation or wind fetch (Schrimpf and Lynch 2021), to provide insight into the mechanisms underpinning habitat selection. The approach we have developed in this study is therefore likely to be applicable to a range of seabirds, in terms of assessing drivers of habitat selection and the tradeoffs that some animals face.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Overall, therefore, our results show that CFD can be used to predict occupancy directly or combined with other approaches, such as the use of orientation or wind fetch (Schrimpf and Lynch 2021), to provide insight into the mechanisms underpinning habitat selection. The approach we have developed in this study is therefore likely to be applicable to a range of seabirds, in terms of assessing drivers of habitat selection and the tradeoffs that some animals face.…”
Section: Discussionmentioning
confidence: 77%
“…Wind regimes are changing in terms of the mean strength and the frequency of extreme weather events ( Young et al 2011 , Young and Ribal 2019 ). Yet most research on how wind affects seabirds has focused on their at-sea behaviour (though see Weimerskirch et al 2012 , Newell et al 2015 , Schrimpf and Lynch 2021 ). We modelled the airflows around our study site to test the role of different wind characteristics in breeding habitat selection and showed that a simple model of airflows and slope angle performed very well for common guillemots, even when applied to the separate island of Skokholm.…”
Section: Discussionmentioning
confidence: 99%
“…Other surface‐nesting seabirds that breed in the sub‐Antarctic, such as giant petrels (Ryan & Bester 2008), are likely to show similar patterns and experience analogous changes to suitable nesting locations in future. More generally, several other seabird species, for example skuas, shags, gulls and terns, all construct nests on the ground surface and occur in environments where wind speeds are relatively high (because of being close to the open ocean, Possner & Caldeira 2017, Schrimpf & Lynch 2021). Therefore, these results could provide insights into where surface‐nesting seabirds nest in general, and how the availability of these sites will be affected by future climatic changes.…”
Section: Discussionmentioning
confidence: 99%
“…Overall therefore, our results show that CFD can be used to predict occupancy directly, or combined with other approaches, such as the use of orientation, or wind fetch (Schrimpf and Lynch, 2020), to provide insight into the mechanisms underpinning habitat selection. The approach we have developed in this study is therefore likely to be applicable to a range of seabirds, in terms of assessing drivers of habitat selection and the trade-offs that some animals face.…”
Section: Predicting Colony Distribution On Skokholmmentioning
confidence: 73%
“…4 Wind regimes are changing, in terms of the mean strength, and the frequency of extreme weather events (Young et al, 2011, Young andRibal, 2019). Yet most research on how wind affects seabirds has focused on their at-sea behaviour (though see (Weimerskirch et al, 2012, Schrimpf andLynch, 2020). We modelled the airflows around our study site to test the role of different wind characteristics in breeding habitat selection, and showed that a simple model of airflows and slope angle performed very well for common guillemots, even when applied to the separate island of Skokholm.…”
Section: Predicting Colony Distribution On Skokholmmentioning
confidence: 94%